KOMPOSISI SPESIES DAN KELOMPOK PAKAN BURUNG DI TAHURA BONTOBAHARI, KABUPATEN BULUKUMBA - Andi Siady Hamzah; Nasri Nasri (Jurnal Eboni, 2021)
Birds are beneficial to the ecosystem because they provide a variety of ecological services. The habitat determines the distribution and community structure of birds. In Tahura Bontobahari, the diversity and feeding guilds of birds were explored. We investigated the species composition, distribution and feeding guild of birds using the count point. We established 26 points for observation in Tahura Bontobahari. Data was collected during September 2019. There were 16 species in total, divided into 14 families. We discovered all species found were devided in six group of feeding guild. Insectivore is the biggest group of feeding guild. We found 6 species of bird as insectivore. All species were not also evenly distributed. Three bird species can only be found in one place